Metode Penafsiran al-Zuhaylî dalam al-Tafsîr al-Munîr - Ainol, Ainol (Mutawatir, 2011)
The first and the foremost authority interprets the Koran is the Prophet Muhammad because he was receiving a direct Koran. After the Prophet, the authority was followed by his companions, tÃ¢biâÃ®n, and mufassir afterward. Interpretations performed above the companions known as tafsÃ®r bi al-maâthur. This commentary underlies the discussion and its source in history. This method became known as a method of interpretation of the Koran is called the method of history. In addition, the method used at that time was the tafsÃ®r bi al-raây underlying source on reasoning and ijtihÃ¢d. One contemporary commentator who try to combine the two sources of the interpretation is Wahbah al-ZuhaylÃ®. The interpretation of the content approached the Koran, from a classic interpretation that many make al-maâthur as the source and from the angle of the many modern and contemporary make raây as the source